Studying the concentration of polymers in blended microplastics using 2D and 3D Raman mapping - Mehrdad Lotfi Choobbari; Jennifer Ferguson; Niko Van den Brande; Tim Smith; Tatevik Chalyan; Wendy Meulebroeck; Heidi Ottevaere (Scientific Reports, 2023)
Abstract The combination of different polymers in the form of blended plastics has been used in the plastic industry for a long time. Nevertheless, analyses of microplastics (MPs) have been mainly limited to the study of particles made of single-type polymers. Accordingly, two members of the Polyolefins (POs) family, i.e., Polypropylene (PP) and Low-density Polyethylene (LDPE) are blended and extensively studied in this work due to their applications in industry as well as abundance in the environment. It is shown that 2-D Raman mapping only provides information about the surface of blended MPs (B-MPs). While complimentary 3-D volume analysis is needed to fully understand the presence of various polymers in such complex samples. Therefore, 3-D Raman mapping is applied to visualize the morphology of the distribution of polymers within the B-MPs together with the quantitative estimation of their concentrations. A parameter defined as the concentration estimate error (CEE) evaluates the precision of the quantitative analysis. Furthermore, the impact of four excitation wavelengths 405, 532, 633, and 785 nm is investigated on the obtained results. Finally, the application of a line-shaped laser beam profile (line-focus) is introduced for reducing the measurement time from 56 to 2 h.